Relevance of [18F]fluorodeoxyglucose positron emission tomography‐positive lymph nodes after neoadjuvant chemotherapy for squamous cell oesophageal cancer. Issue 11 (4th September 2013) - Miyata, H.; Yamasaki, M.; Takahashi, T.; Murakami, K.; Kurokawa, Y.; Nakajima, K.; Takiguchi, S.; Mori, M.; Doki, Y.
<x xml:space="preserve">Abstract</x> Background Several studies have examined the clinical significance of metabolic response in primary tumours by [18F]fluorodeoxyglucose positron emission tomography (18F‐FDG‐PET) in patients with oesophageal cancer who undergo neoadjuvant therapy. The relevance of the metabolic response in lymph nodes is unclear. Methods Consecutive patients with oesophageal cancer who underwent neoadjuvant chemotherapy followed by surgery were studied. 18F‐FDG‐PET was performed before and 2–3 weeks after completion of neoadjuvant chemotherapy, assessing FDG uptake in primary tumours and lymph nodes considered to be metastatic. Results Before therapy, 156 (73·9 per cent) of 211 patients had PET‐positive nodes, of whom 89 (57.1 per cent) had no evidence of metabolic activity in these lymph nodes following chemotherapy. There was a significant relationship between post‐treatment lymph node status assessed by FDG‐PET and numbers of pathologically confirmed metastatic lymph nodes. Patients with post‐treatment PET‐positive nodes had shorter survival than those without (5‐year survival rate 25 versus 62·6 per cent; P < 0·001). There was no difference in survival between patients with PET‐positive nodes before but not after therapy and patients who had PET‐negative nodes throughout (5‐year survival rate 59 versus 71 per cent respectively; P = 0·207). Multivariable analysis identified post‐treatment nodal status assessed by FDG‐PET and tumour depth as independent prognostic factors. Conclusion Identification of PET‐positive lymph nodes after completion of chemotherapy is a predictor of poor prognosis of patients with oesophageal cancer scheduled for surgery. FDG‐PET lymph node status after neoadjuvant chemotherapy is more important than that before chemotherapy.